2010
DOI: 10.1016/j.joca.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pattern and determinants of radiographic hand osteoarthritis in five Russian community-based samples

Abstract: Significant differences in prevalence and severity of hand OA were found between the Russian samples living in different geographic areas. Additional studies are needed to discover the mechanism defining the association between places of residence and development of hand OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…A high prevalence of MCP OA has been found in rural communities from the former Soviet Union 14 15. The discrepancy between these and other populations (including Framingham) may be due to differences in disease-susceptibility genes or occupational/cultural lifestyles, as MCP OA has been associated with heavy labour 32.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of MCP OA has been found in rural communities from the former Soviet Union 14 15. The discrepancy between these and other populations (including Framingham) may be due to differences in disease-susceptibility genes or occupational/cultural lifestyles, as MCP OA has been associated with heavy labour 32.…”
Section: Discussionmentioning
confidence: 99%
“…MCP involvement is generally thought to be less common than other hand joints and to represent a secondary OA process such as calcium pyrophosphate deposition disease (CPPD) or hemochromatosis. However, as shown by several studies reporting the patterns of hand OA, MCP involvement is not infrequent in radiographic or ultrasonographic OA [6,30], with prevalence estimates ranging from 8% to 36% in Caucasian populations [9,31-33]. MCP rOA has been shown to be more common among African American compared with white women in one study [34].…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study [17], we found a significant difference in prevalence and severity of hand OA between five Russian samples (same ethnicity) living in different areas. Similarly, a study of the Chinese Han population showed that the prevalence of symptomatic and radiographic knee OA differs between South China and North China [10], with a much lower prevalence in South China.…”
Section: Discussionmentioning
confidence: 72%